Kajian kualitas air dan strategi pengelolaan Rawa Jombor, Klaten, Jawa Tengah - Rina, Timotius Ragga; Purnama, Setyawan; Nugroho, Andhika Puspito (Universitas Gadjah Mada, 2023)
Rawa Jombor is a semiartificial reservoir whose contruction are works for serving the needs of irrigation in the dry season and as a floading control in the rainy season. Rawa Jombor also used for fish farming and floating restaurant by the community. The existence of the cages and floating restaurant can have a negative impact to the aquatic environment due to the disposal of waste and leftover food and metabolism that is deposited at the bottom of the water. This study aims to analyze the water quality, pollution levels and to develop a management strategy of Rawa Jombor. Water quality is measured at 9 sampling point determined by purposive sampling based on the use of Rawa Jombor. Pollution level is analized uses pollution index and the management strategy uses analytical Herarchy Process. The results show that Rawa Jombor has decreased water quality marked by several parameters that do not meet the class III of water quality standards according to Government Regulation No. 82 of 2001. Rawa Jombor is included in the category of mildly polluted in areas without activity, floating restaurant and fish cage for water allotment class I, II, III and IV with an average pollution index ranging from 1,02 to 2,886. To maintain the continuity of the Rawa Jombor, a management strategy with priority on the economic aspects is needed with the development of the Rawa Jombor for sustainable fisheries.